Oxidative Stress in Postoperative Atrial Fibrillation: Does Malondialdehyde Hold Predictive Value? - Urska Intihar; Arta Krasniqi; Anze Djordjevic; Jan Zmazek; Harun Avdagic; Jus Ksela; Miha Antonic (Medicina)
Background and Objectives: Postoperative atrial fibrillation (POAF) is a common complication following cardiac surgery, associated with increased morbidity and prolonged hospital stays. Oxidative stress has been implicated in POAF pathogenesis, with malondialdehyde (MDA), a marker of lipid peroxidation, proposed as a potential biomarker. However, conflicting evidence exists regarding its predictive value. This study aimed to assess the association between serum MDA levels and POAF incidence in patients undergoing cardiac surgery. Materials and Methods: This prospective observational study included 99 consecutive patients undergoing elective on-pump cardiac surgery. Patients with preoperative atrial fibrillation, chronic kidney disease requiring dialysis, or emergency surgery were excluded. Blood samples for MDA measurement were collected at six perioperative time points: preoperatively, intraoperatively after aortic clamp release, and at 8, 24, 48, and 72 h postoperatively. Patients were monitored for new-onset POAF during the first three postoperative days. Statistical analyses included independent samples t-tests, Mann–Whitney U-tests, and Fisher’s exact tests, with significance set at p < 0.05. Results: POAF occurred in 33 (33%) patients. Patients who developed POAF were significantly older (p = 0.017) and had higher EuroSCORE II values (p = 0.019). No significant differences were observed in serum MDA concentrations between POAF and non-POAF patients at any measured time point. The incidence of POAF was higher in patients undergoing valvular surgery (p = 0.014). Conclusions: Serum MDA levels were not associated with POAF development, suggesting that lipid peroxidation alone may not play a central role in POAF pathogenesis. These findings challenge the predictive value of MDA for POAF risk stratification. Future research should explore alternative oxidative stress markers and their potential therapeutic implications in POAF prevention.